Integral characteristics of absolute and relative silo vibrations under seismic influencev. - Шпачук, Володимир Петрович; Засядько, Микола Андрійович; Гарбуз, Алла Олегівна; Абракітова, Анна Юріївна (Eastern-European Journal of Enterprise Technologies, 2014)
The results of investigating the dependence of integral quadratic values of the absolute acceleration and relative shift of a silo body on structural characteristics of the body, columns and seismic influence parameters have been presented in the article. The task of minimization of integral quadratic relative shift of silo by choosing damping coefficient has been solved. The expressions for the optimum value of damping coefficient and integral quadratic criterion as a function of maximum value of absolute acceleration have been obtained. The mathematic model and optimum value of damping coefficient allow to determine structural parameters of bearing silo structure and therefore to provide specified indices of its vibration resistance, vibration strength and durability in use. Graphic dependences of values of integral quadratic absolute acceleration and integral quadratic relative shift of a silo body at modifying the amplitude of seismic influence and the coefficient of relative damping of columns, silo mass and the value of its integral quadratic absolute acceleration have been presented. The data obtained are expected to be used in designing new and modification silo samples, high buildings and structures maintained in seismic zones as well as when developing and introducing active and passive means of damping them.